IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KABUPATEN/KOTA LAYAK ANAK (KLA) DI KOTA PALEMBANG - Amir Mahmud; Suandi Suandi (MAP Program Pascasarjana Universitas Sjakhyakirti, 2020)
Implementation of Child Friendly Cities Development Policy is one way to create an environment that can guarantee fulfillment of children's rights carried out by the government together with the community and the business world. In Indonesia, cases of violations of children's rights are increasingly prevalent, especially cases of violence against children. The purpose of this research is to determine Implementation of Child Friendly Cities Development Policy in Palembang City. This research use methode is qualitative methode. This research used policy implementation theory by Van Metter and Van Horn in Agustino (2008). Data collection techniques which used are interview, observation and documentation. Data analysis which used is data reduction, display data, and conclusion. The triangulation technique used to check the validity of the data in this research is the source and method triangulation. The result shows that the implementation of Child Friendly Cities Development Policy in Palembang is generally good, seen from the achievement of the objectives policy with the fulfillment of the majority of children's rights under the Convention on the Rights of the Child (KHA), although there are some things still need to be improved, namely the characteristics of implementing agencies, inter-organizational communication and implementing activities, as well as the economic, social and political environment.